IMPLEMENTASI PRINSIP DASAR AKUNTANSI PADA LAPORAN KEUANGAN USAHA MIKRO, KECIL DAN MENENGAH(UMKM) DI KELURAHAN PELA MAMPANG - Intan Damawati; Octaviana, Vinna; Suharto (Jurnal Ilmiah Satyagraha, 2025)
It is undeniable that the presence of MSMEs has a positive impact on the people's economy. Of course, with this positive impact, MSME actors must be aware of the importance of implementing an accounting system in running their business. This article wants to discuss the extent to which the application of the accounting recording system is carried out by MSME actors in Pela Mampang Village. This article uses accounting theory or concepts. This article also uses a qualitative research method with data collection techniques from primary sources by interviewing several MSME actors at the research location and secondary from books and journals. This article concludes that there are still many MSME actors in Pela Mampang Village who do not realize or understand the importance of an accounting recording system in running their business. They only do simple recording. There are several obstacles faced by them, including limited understanding, the accounting recording system is considered complicated and unimportant, the low level of education of MSME actors, and no initiative to take part in recording training according to accounting standards.